Mechanical properties of hybrid fiber reinforced coral concrete. (June 2022) - Liu, Bing; Zhang, Xuanyu; Ye, Junpeng; Liu, Xiaoyan; Deng, Zhiheng
Abstract: This paper investigated the effect of microfibers (carbon fibers and basalt fibers) and macrofibers (plastic steel fibers) on the mechanical properties of coral concrete. A total of 192 specimens were designed with carbon fibers (CFs), basalt fibers (BFs), and plastic steel fibers (PSFs) as variables. The compressive strength, splitting tensile strength, axial compressive strength, and elastic modulus of hybrid fiber-reinforced coral concrete were studied by testing. The results show that all three fibers can improve the mechanical properties of coral concrete. The microfiber major positively affects the stage before the macrocracks are formed, and the positive effect of macrofibers major works on the stage after the macrocracks are appeared. Hybrid addition of microfibers and macrofibers can further improve the mechanical properties. The cube compressive strength, splitting tensile strength, axial compressive strength, and elastic modulus can be improved by 11.2%, 25.5%, 14.1%, and 8.5%, respectively, when incorporating the optimum hybrid fiber dosages (CFs 0.15%, BFs 0.15%, and PSFs 4 kg/m 3 ).